Two Cosmological Hypotheses: The Friedmann-Planck Micro-Universes for Vacuum Particles, The Schwarzschild Photon Spheres for Elementary Particles - Fèvre, Raymond; Dijon, France (European Journal of Applied Sciences, 2021)
This article presents in a synthetic way two articles published in JHEPGC ([1], [2]) and develops some aspects. Two hypotheses are studied. In the first one, the vacuum is endowed with a quantum structure in which the vacuum particles are Friedmann-Planck micro-universes. For this, the article introduces a quantization of a closed Friedmann universe, then a quantization of the photon spheres filling this universe. This approach gives a numerical value consistent with cosmological measurements for the current dark energy density of our Universe. Next, the second hypothesis takes the content of a model published in Physics Essays in 2013 [3], assuming that elementary particles are Schwarzschild photon spheres; these could be derived from the Friedmann photon spheres composing the vacuum particles. It is further recalled that the model presents a unified structure of elementary particles and allows us to calculate the value of the elementary electric charge as well as the mass of the elementary particles. Finally this article summarizes a model of closed universe described in reference [2]